Balancing between efficiency and equity in publicly funded health systems - Cerović, Ljerka (Mednarodna revija za javno upravo, 2017)
The purpose of this paper is to provide a theoretical overview of efficiency and equity and give insights in the Croatian health system. Using selected indicators, a basic descriptive review of efficiency and equity in the Croatian health system was made, with an added comparison to other countries of the European Union. Observed at the macro level, Croatia shows relatively good efficiency of its health system, even above average of the comparable countries by health expenditure per capita, but still significantly below the most developed EU countries. Still, Croatia requires further reforms that would enhance efficiency of its health system (especially at the hospital level), without sacrificing equity which is a fundamental right of all citizens in need of health care. Although, in total only small proportion of the population perceived an unmet need for health care, Croatia reported much larger inequalities in unmet need among different socio-economic groups, between high and low educated population, between women and men and among different age groups.
Keywords: Croatia; health systems; Hrvaška; javni sektor; javno zdravstvo; public health system; zdravstveni sistemi